1998
DOI: 10.1037/0012-1649.34.3.565
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in 8- to 18-month old drug-exposed infants.

Abstract: This study examined the cognitive functioning in 236 infants at 8 and 18 months of age. Thirty-seven infants were heavily exposed to cocaine in-utero, 30 were lightly exposed, and 169 were not exposed to cocaine. Cognitive functioning was evaluated with the Bayley Scales of Infant Development (2nd ed.; N. Bayley, 1993) at both ages. Infant information processing was also assessed with an infantcontrolled habituation procedure. Results indicated that (a) infants of cocaine-abusing women had higher neonatal medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 45 publications
(75 reference statements)
6
71
2
Order By: Relevance
“…This association between PCE and motor development has been reported previously by some researchers [34,82], but not by others [2,4,43,58]. This is an area that is in need of further investigation.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This association between PCE and motor development has been reported previously by some researchers [34,82], but not by others [2,4,43,58]. This is an area that is in need of further investigation.…”
Section: Discussionmentioning
confidence: 81%
“…Most investigators have also not found detrimental effects of PCE on infant motor development, as measured by the Psychomotor Development Index (PDI) of the BSID or by the Peabody Developmental Motor Scales [2][3][4]12,13,21,34,36,41,43,[58][59][60]65,83]. By contrast, Singer et al [82] found that PCE was associated with lower PDI scores at about 17 months.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous studies reporting findings from exposed offspring have linked prenatal cocaine exposure with microcephaly (5), low birth weight and preterm births (6), altered or delayed motor development (7), global hypertonia and coarse tremor (8), reduced cognitive development (9), and a subtle reduction in IQ (3) in a subset of exposed offspring. However, the data remains elusive as to the independent contribution of prenatal cocaine vs. confounding variables such as poly-drug use, poor prenatal; care, adverse living situations, and compromised maternal health in contributing to adverse postnatal neuro-behavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of studies have noted that the caregiving environment of children exposed to cocaine and other substances in the prenatal period is often unstable and negative (Alessandri, Bendersky, & Lewis, 1998;Brown, Bakeman, Coles, Platzman, & Lynch, 2004;Singer et al, 2002). This is especially important given recent reports that cocaineexposed children in nonmaternal, nonkin care in the first 2 years of life have more positive outcomes at 2 years of age compared with those raised by their biological parent (Brown et al, 2004).…”
Section: Discussionmentioning
confidence: 99%